The effect of resistance exercises performed at home on swimming performance of adolescent swimmers during the covid-19 pandemic period - Umay, Büşra; Atar, Özdemir; Koç, Hürmüz (VIREF Revista de Educación Física, 2022)
Aim: to examine the effect of resistance exercises performed at home on swimming performance in adolescent swimmers during the COVID-19 pandemic period. Method: a total of 114 adolescent swimmers aged between 10-17 years, (N=66) male and (N= 48) female, performing at the Turkish Olympic Preparation Center (TOHM) participated in the research voluntarily. The research was designed as a quasi-experimental study, since there was no control group. The resistance exercise program, which was performed at home for 8 weeks during the pandemic period, was applied for the athletes participating in the research through video conference method and by expert swimming trainers. The pre-test swimming degrees of the athletes were requested from the institution with the archive scanning method, and the post-test values were taken by the expert swimming trainer after the applied training program. To determine the effect of the applied training program, 50m, 100m, 200m and 400m swimming degrees of the athletes were determined in the pool environment with the Castimolap D-308 hand chronometer. The data obtained as a result of measurement, calculation and tests in the research were analyzed in the SPSS 22.00 statistical analysis software. Paired-Samples T test was applied to determine the difference between pretest and posttest in the statistical analysis. The significance level was accepted as p<0.05. Results: as a result of the statistical analysis, a statistically significant difference was determined between the freestyle swimming degrees (50-100-200-400m) pre-test and post-test values of the athletes. Conclusion: our results demonstrated that resistance exercises performed at home did not have a positive effect on swimming performance. In this respect, it is very important for the athletes in the swimming performance group to train in the pool environment in order to maintain and improve their performance.